Development of Sparkol Video Media in the Course of Anti-Corruption Education - Hasni Hasni; I Ketut Linggiha (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to determine the validity and practicality of video media in the ian University in Indonesia. This research utilizes the ADDIE research approach (Analysis, Design, Development, Implementation, and Evaluation). The results of validity and practicality tests may be used as a reference for evaluating the developed medium. This study conducted a material validity test, assessing the quality of the video media based on expert material evaluations. The results showed an average rating of 97.5%. Therefore, the video media meets the criteria for being deemed suitable for use. The results of the media validity test indicate that the quality of the video media, as assessed by media experts, has an average score of 97.06%. Therefore, the video media meets the criteria for being deemed suitable for use. The results of the validity test for video media in the course of anti-corruption education indicate that the content and media are very relevant for further development. The practicality test results indicate that the development of interactive media achieved an average of 97%. Thus, the module demonstrates efficient criteria.